The Regional Application of the Global Entrepreneurship and Development Index (GEDI): The Case of Spain - Ács, Zoltán J.; Szerb, László; Ortega-Argilés, Raquel; Aidis, Ruta; Coduras, Alicia (Regional studies, 2015)
Ács Z. J., Szerb L., Ortega-Argilés R., Aidis R. and Coduras A. The regional application of the Global Entrepreneurship and Development Index (GEDI): the case of Spain, Regional Studies. This paper constructs a regional application of the Global Entrepreneurship and Development Index (GEDI) that captures the contextual features of entrepreneurship across regions. Using institutional data and survey data, weaknesses in the incentive structure that affect regional development can be identified. The entrepreneurial disparities among regions are analysed at the country and regional levels using a penalty for bottleneck methodology. The methodology allows public policy action to be coordinated at both national and regional levels. It is found that GEDI provides a valuable tool for understanding regional differences across Spanish regions.